PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI - Bambang Sumaryanto, 13.52.02.0020; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of motivation and dicipline on teacher performance with organizational culture variabel moderating. The population in this study is the elementary teachers, in GunemÂ Rembang many as 113 responden. Data were collected using a questionnaire, after which the data were processed using SPSS 17. Test instruments used are validity and reliability . While ui model used is the coefficient of determination and test FÂ . Test this hypothesis using regression analysis. Result of research analysis express that motivation has positive influence and significant to teacher performance, dicipline doesnât positive influence and significant to teacher performance, organizational culture doesnât positive influence and significant to teacher performance, organizational commitment has variabel moderating. Keywords: Motivation, dicipline, organizational culture, teacher Performance